2019
DOI: 10.1186/s12879-019-3975-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and safety of dolutegravir relative to common core agents in treatment-naïve patients infected with HIV-1: a systematic review and network meta-analysis

Abstract: Background Network meta-analyses (NMAs) provide comparative treatment effects estimates in the absence of head-to-head randomized controlled trials (RCTs). This NMA compared the efficacy and safety of dolutegravir (DTG) with other recommended or commonly used core antiretroviral agents. Methods A systematic review identified phase 3/4 RCTs in treatment-naïve patients with HIV-1 receiving core agents: ritonavir-boosted protease inhibitors (PIs), non-nucleoside reverse tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
37
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 83 publications
8
37
0
4
Order By: Relevance
“…Network meta-analysis (NMAs) allows comparison of individual core agents, based on a network of randomized clinical trial evidence, where head to head data are unavailable. A recent meta-analysis compared these core agents on efficacy outcomes such as VS and CD4+ cell count change from baseline, and safety outcomes including adverse events [AEs], discontinuations, discontinuation due to AEs and lipid changes [6]. Authors concluded INSTIs to have superior efficacy and comparable safety to PIs and NNRTIs with DTG being among the most efficacious INSTI in treatment-naïve HIV-infected patients.…”
Section: Introductionmentioning
confidence: 99%
“…Network meta-analysis (NMAs) allows comparison of individual core agents, based on a network of randomized clinical trial evidence, where head to head data are unavailable. A recent meta-analysis compared these core agents on efficacy outcomes such as VS and CD4+ cell count change from baseline, and safety outcomes including adverse events [AEs], discontinuations, discontinuation due to AEs and lipid changes [6]. Authors concluded INSTIs to have superior efficacy and comparable safety to PIs and NNRTIs with DTG being among the most efficacious INSTI in treatment-naïve HIV-infected patients.…”
Section: Introductionmentioning
confidence: 99%
“…Amongst third agents, INSTIs are the most preferred as evident in studies that showed it be superior or equivalent to other third agents in safety and efficiency. In addition, it is reported that INSTIs are more tolerable to patients, in turn reducing discontinuation rates [20][21][22][23]. However, for patients that are at higher risk of non-adherence, PIs as the third agent would be most appropriate because of their genetic barrier to resistance [24].…”
Section: Introductionmentioning
confidence: 99%
“…Since 2007, antiretroviral therapy (ART) regimens based on an integrase strand transfer inhibitor (INSTI) have been introduced and largely used both in treatment-naïve and treatment-experienced people because of their safety and efficacy, as demonstrated in many clinical trials and observational studies [ 1 , 2 ]. The widespread use of INSTI-based regimens, particularly first-generation agents, has led to the emergence of INSTI resistance in a limited proportion of people with HIV-1 infection (PWH) [ 3 ].…”
mentioning
confidence: 99%